2016
DOI: 10.1016/j.chemosphere.2016.05.047
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cement dust pollution on Cedrela fissilis Vell. (Meliaceae): A potential bioindicator species

Abstract: Considering the impacts caused to vegetation in the vicinity of cement factories, the aim of this study was to evaluate the impacts of cement dust on the structural organization and physiological/biochemical traits of Cedrela fissilis leaflets, a woody species native to tropical America. Plants were exposed to 2.5 or 5 mg cm-2 cement dust applied to the leaf surface, to the soil or simultaneously to the leaf surface and the soil.. Leaves of shoot-treated plants exhibited chlorosis, marginal and inter veins nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 44 publications
2
9
0
Order By: Relevance
“…SOD catalyzes the dismutation of superoxide into oxygen and hydrogen peroxide (Tyagi et al, 2019). Consistent with our results, several studies reported that SOD activity increased in response to dust deposition in plants (Erdal & Demirtas, 2010;Siqueira-Silva et al, 2017;Siqueira-Silva et al, 2016). POD, another antioxidant enzyme, is broadly distributed among plant tissues and plays a significant role in various growth, development, and senescence processes.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…SOD catalyzes the dismutation of superoxide into oxygen and hydrogen peroxide (Tyagi et al, 2019). Consistent with our results, several studies reported that SOD activity increased in response to dust deposition in plants (Erdal & Demirtas, 2010;Siqueira-Silva et al, 2017;Siqueira-Silva et al, 2016). POD, another antioxidant enzyme, is broadly distributed among plant tissues and plays a significant role in various growth, development, and senescence processes.…”
Section: Discussionsupporting
confidence: 89%
“…Investigations on dust have mainly focused on the impacts of the different kinds of dust on morpho-physiological changes in plants (Drack & Vázquez, 2018;Hatami et al, 2018;Siqueira-Silva et al, 2017;Siqueira-Silva et al, 2016). Stone crusher dust led to a decrease in grain yield of rice (Oryza sativa.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence of POD and APX's role in scavenging H 2 O 2 , an increase in POD and APX activities can be regarded as a defence mechanism of the plant against the reinforcement of oxidative processes. Dust accumulation on plants might alter the leaf antioxidant mechanism (Chaturvedi et al 2013), and increased APX activity under dust pollution has been reported by Siqueira-Silva et al (2016).…”
Section: Discussionmentioning
confidence: 99%
“…Dust pollution causes a progressive reduction in the photosynthetic ability of leaves and in the growth and productivity of plants, leading to a probable change in morphological characteristics, photosynthetic pigment concentration and/ or relationships, as well as in the antioxidant mechanism of leaves (Younis et al 2013, Gupta et al 2015. Closure of leaf stomata and a reduction in stomatal conductance (Siqueira-Silva et al 2016), an increase in leaf temperature and collapse of the leaf cuticle layer have been reported as the negative impacts of dust pollution (Naidoo and Chirkoot 2004). Rai (2016), on the other hand, reported leaf shading, blocking of stomata, transpiration rate reduction and increase in leaf temperature as the problems with dust deposition in plants leading to a direct decline in the photosynthetic rate.…”
Section: Introductionmentioning
confidence: 99%
“…The equivalent reductions for the two hybrid options are 23% and 11%. These reductions are ascribed to the lower amount of dust generated by the petroleum coke mill, as less or no fuel is consumed by the solar systems (Siqueira-Silva et al 2016, Khaniabadi et al 2018.…”
Section: Particulate Matter Formation (Pmf) and Terrestrial Acidification (Ta)mentioning
confidence: 99%